Clinical significance of PD-L1-positive cancer-associated fibroblasts in pN0M0 non-small cell lung cancer. (November 2019) - Teramoto, Koji; Igarashi, Tomoyuki; Kataoka, Yoko; Ishida, Mitsuaki; Hanaoka, Jun; Sumimoto, Hidetoshi; Daigo, Yataro
Highlights: Cancer-associated fibroblasts (CAFs) play critical pro-tumorigenic roles in tumor stroma. PD-L1 expression on CAFs is reversibly regulated by IFN-γ released from activated lymphocytes. In pN0M0 NSCLC, postoperative RFS is significantly longer in patients with PD-L1 + CAFs. PD-L1 expression on CAFs is an independent prognostic factor of higher 5-y RFP in pN0M0 NSCLC. Abstract: Objectives: Cancer-associated fibroblasts (CAFs) are a dominant cell type in tumor stroma and support the generation of pro-tumorigenic microenvironment. CAFs have frequent opportunities to interact with immune cells infiltrating the tumor stroma, but the process remains to be determined. In this study, we focused on immune checkpoint mechanism. We also examined the induction of programmed cell death-ligand 1 (PD-L1) on CAFs by immune cell, and the clinical significance of PD-L1-expressed CAFs in non-small cell lung cancer (NSCLC). Materials and methods: CAFs were isolated from human NSCLC tissues, and PD-L1 expression levels in CAFs were analyzed by real-time polymerase chain reaction and flow-cytometry. Following immunohistochemical analysis of PD-L1 in surgically resected pN0M0 NSCLC (n = 125, including 88 invasive adenocarcinomas and 37 squamous cell carcinomas), the correlation of PD-L1-positive CAFs with clinicopathological features was investigated. Results: PD-L1 mRNA and protein expression on CAFs was upregulated by exogenously supplemented interferon-gamma (IFN-γ) and downregulated through the depletion of IFN-γ. PD-L1 expression on CAFs was upregulated by co-culture with activated lymphocytes releasing IFN-γ. Immunohistochemistry revealed that PD-L1-positive CAFs were observed in 31 cases (24.8%). Postoperative relapse-free survival was significantly prolonged in patients with PD-L1-positive CAFs as compared with those with PD-L1-negative CAFs, with 5-year relapse-free probabilities of 84.5% and 66.3%, respectively ( P  = 0.031). Multivariate analysis revealed that PD-L1 expression on CAFs was an independent prognostic factor of longer relapse-free survival after surgery (hazard ratio: 3.225, P  = 0.027). Conclusion: PD-L1 expression on CAFs is reversibly regulated by environmental stimuli including IFN-γ from activated lymphocytes. In the non-metastatic NSCLC, PD-L1 expression on CAFs suggests the induction of anti-tumor immune responses, contributing to better prognosis after surgery.